2016
DOI: 10.1159/000450945
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology of Aging: A Mini-Review

Abstract: Aging is generally associated with weakening of the circadian system. The circadian amplitude is reduced and the circadian acrophase becomes more labile, tending to occur earlier with advancing age. As originally noted by Franz Halberg, similar features are observed in the experimental laboratory after bilateral lesioning of the suprachiasmatic nuclei, suggesting the involvement of clock genes in the aging process as they are in various disease conditions. Recent work has been shedding light on underlying path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 41 publications
2
43
0
1
Order By: Relevance
“…Circadian rhythm is a tightly regulated internal biological clock, which modulates various physiological processes and undergoes changes with age [111][112][113][114]. In particular, dysregulation of circadian rhythm is associated with alterations in metabolism and development of cancers [115][116][117].…”
Section: Box 3 Crtcs In Circadian Rhythmmentioning
confidence: 99%
“…Circadian rhythm is a tightly regulated internal biological clock, which modulates various physiological processes and undergoes changes with age [111][112][113][114]. In particular, dysregulation of circadian rhythm is associated with alterations in metabolism and development of cancers [115][116][117].…”
Section: Box 3 Crtcs In Circadian Rhythmmentioning
confidence: 99%
“…We classify this sub-heading as being part of the process of senescence (natural ageing) or senility (pre-disease or during disease) [ 2 ], though temporal changes between the two states is often difficult to establish because of the experiment design which often focuses on the duration of study and required outcomes and confounding factors such as the inclusion/exclusion characteristics of the recruits to clinical trials (e.g., Body Mass Index (BMI), health definitions, birth cohort, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…found that 43% of all protein-coding genes showed circadian oscillations in transcription somewhere in the body, largely in an organ-specific manner 8 . Additionally, the functionality of the circadian clock is attenuated or disrupted with age 9 , 10 . As a consequence, the disruption of the circadian clock has been associated with a variety of physio-pathological states, ranging from metabolic disorder to cancer.…”
Section: Introductionmentioning
confidence: 99%